Strategies used and cultural considerations in seeking advice on in-vitro fertilisation online: a case of Malaysian women - Jariah Mohd Jan,; Chiew, Pung Wun (Penerbit Universiti Kebangsaan Malaysia, 2016)
Despite the growing literature on computer-mediated communication (CMC), the online communicative behaviour of specific communities remains largely unexplored. This paper aims to contribute to the existing body of literature by examining the strategies Malaysian women use when seeking advice related to in-vitro fertilisation (IVF) in CMC. Messages posted in an online forum were analysed using the web content analysis method. The results of the study reveal that the advice-seeking strategies of the Malaysian women are tied in closely with their culture. This is largely shown in how the messages were constructed, as well as in the message content itself. As such, the findings suggest that despite the anonymity afforded by CMC, elements of cultural influence are still detectable in the ways Malaysian women seek advice online.